Gods, heroes, saints, and friends: ethical exemplarism and practical paideia in Gregory Nazianzen and his peers - Lapsa, BM (2023)
In this thesis I analyse the uses of ethical exemplarism in Gregory of Nazianzus and several of his contemporaries: his friends and Cappadocian compatriots, Basil of Caesarea and Gregory of Nyssa, and Emperor Julian the Apostate. I begin by surveying a selection of their writings and those of other authors active in the fourth-century culture wars, analysing the frequency of exempla (incidents featuring a moral exemplar) found therein, as well as the cultural and historical origins of those exempla (Chapter 1). Besides filling a lacuna noted by Demoen (1996), this chapter indicates our authors’ favoured periods of reference and suggests new avenues of analysis. Next, I connect educational practices known from literary sources and recent papyrological finds to the ways in which Nazianzen and others employed exemplars as models of particular virtues and vices (Chapter 2). There I also present a selective analytical catalogue of the gods and mythical heroes of Hellenic culture as found in Nazianzen, Basil, Nyssen, and Julian (Chapter 2). I then turn to the uses they made of a number of secular historical exemplars, selected in part on the basis of appearances in Plutarch’s Lives and Valerius Maximus’ Facta et dicta (Chapter 3). I next apply the same method to prominent figures from Scripture, here starting from the virtue-exemplar associations in Hebrews 11 and 1 Clement (Chapter 4). Chapters 2–4 together comprise the most thorough catalogue and analysis to date of heroes and villains in Julian and the Cappadocians. Finally, I assess Nazianzen’s presentation of exemplars to reconstruct his vision of how aspiring ethical agents are meant to apply their knowledge of models of virtue and vice in practice, and his thoughts on how ethical exemplarism can go wrong (Chapter 5). Against the backdrop of recent work on exemplars in Roman history (Langlands [2018], Roller [2018]) and contemporary metaethics (Zagzebski [2017]), this last chapter provides a much-needed perspective from the late ancient Hellenic world as well as a new framework for understanding the experience of ethical exemplarism more generally. Taken as a whole, this dissertation illuminates the workings of the moral imagination during a period of crisis in Late Antiquity, provides a novel framework for a developing branch of historical and contemporary ethics, and demonstrates the utility of exemplar analysis as a method for understanding cultural priorities and cultural change.